2000
DOI: 10.1016/s0741-5214(00)90100-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of ischemic heel ulceration and gangrene: An evaluation of factors associated with successful healing

Abstract: The objective of this study was to determine the effectiveness of treatment of nonhealing heel ulcers and gangrene and to define those variables that are associated with success. Methods: A multi-institutional review was undertaken at four university or universityaffiliated hospitals of all patients with wounds of the heel and arterial insufficiency, which was defined as absent pedal pulses and a decreased ankle/brachial index (ABI). Risk factors, hemodynamic parameters, and arteriographic findings were statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 18 publications
(12 reference statements)
1
38
3
Order By: Relevance
“…13 It is worth emphasizing that we did not observe any specific characteristics in the ischemic lesions that were correlated with the mechanism of lesion formation (i.e., spontaneous or secondary to external aggression).…”
Section: Discussionmentioning
confidence: 51%
“…13 It is worth emphasizing that we did not observe any specific characteristics in the ischemic lesions that were correlated with the mechanism of lesion formation (i.e., spontaneous or secondary to external aggression).…”
Section: Discussionmentioning
confidence: 51%
“…In our cohort of 192 patients undergoing revascularisation, 13% (24 patients) had chronic renal insufficiency according to our criteria, representing a substantial proportion of our clinical case burden. We used a defining criterion for renal impairment of a serum creatinine value greater than 150 mmol/L, as used by other authors [7,9]; our criterion differed slightly from theirs by only including those patients who had recorded elevated serum creatinine on two occasions, three months apart, prior to surgery, in order to ensure that renal impairment was long-standing. The use of this selection criterion led to the inclusion of a majority of cases who were not receiving any renal support at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving active renal support by haemodialysis, or continuous ambulatory peritoneal dialysis, or who had a serum creatinine value >150 mmol/L (1.7 mg/dL), on at least two separate occasions, three months apart, prior to surgery, were regarded as having chronic renal impairment. A single serum creatinine value has been used by other authors as an inclusion criterion for CRI in similar studies [7,9], but we only included patients with elevated serum creatinine on at least two occasions, to ensure that renal impairment was longstanding. Due to the retrospective nature of the study, the absence of 24-hour urine volume data made it impossible to calculate creatinine clearance, for example, using the Cockcroft-Gault equation.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for this suggested differentiation is that we assume from our general clinical observations that gangrene with large tissue lost always causes a poorer survival than dry necrosis, regardless of whether the patients have been revascularized or not. However, this assumption is controversially debated in the literature, with some authors supporting it [8,9] and others not supporting it [2].…”
Section: Discussionmentioning
confidence: 99%
“…Georgopoulos et al [1] have found that the limb salvage rate in patients with ESRD and diabetes justifies limb revascularization, despite the decreased survival of this population. Treiman et al [2] stated that patients with impaired renal function are at increased risk for treatment failure due to potential impaired wound healing, but they nonetheless should not be denied revascularization surgeries, since the wounds may successfully heal. However, other investigators found that risk of death was higher after bypass surgery [3], especially after consecutive limb loss [4], and the risk of amputation increased depending on the procedure type and the diabetes status.…”
Section: Zusammenfassung Einfluss Der Femoropoplitealen Bypassoperatimentioning
confidence: 99%